Study the relationship between medical sciences students' self-esteem and academic achievement of Guilan university of medical sciences - Maryam Mirzaee Jirdehi; Fariba Asgari; Rasool Tabari; Ehsan Kazemnejad Leyli (Journal of Education and Health Promotion, 2018)
Background: Achievement of productivity and improvement of quality in the educational system is the effective, influential factors for countries development. Academic achievement is the main objective of the training program and the most important concerns of teachers, education officials, and university Student's families. Self-esteem is one of the factors affecting student academic achievement. This study is aimed to investigate the relationship between self-esteem and academic achievement in Medical Sciences students of in 2014–2015. Subjects and Methods: This is a descriptive–correlational study. In this study, 537 university students were selected using random stratified sampling method from Guilan University of Medical Sciences in 2014–2015. Data were collected using the standard self-esteem questionnaire of Cooper Smith consisting of four elements (general, social, familial, and educational) and a demographic questionnaire. Data were analyzed using SPSS software version 21 and descriptive statistics such as Spearman correlation and Logistic Regression. Results: The results indicated a significant relationship between grade point average and educational self-esteem (P = 0.002, r = 0.135) and global self-esteem (P = 0.02, r = 0.102). There was also a significant relationship between composite Index educational status and general self-esteem (P = 0.019, r = 0.102) and academic achievement (P = 0.007, r = 0.116) and global self-esteem (P = 0.020, r = 0.102). Conclusions: According to the results, the highest mean score of self-esteem was related to the familial element, and the lowest average was in terms of social self-esteem, therefore, given the importance and necessity of self-esteem in academic achievement, strengthening of all aspects of self-esteem is suggested.